2021
DOI: 10.1136/bmjopen-2021-053806
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilisation and costs associated with a heart failure diagnosis: a retrospective, population-based cohort study in Sweden

Abstract: ObjectivesTo examine healthcare resource use (HRU) and costs among heart failure (HF) patients using population data from Sweden.DesignRetrospective, non-interventional cohort study.SettingTwo cohorts were identified from linked national health registers (cohort 1, 2005–2014) and electronic medical records (cohort 2, 2010–2012; primary/secondary care patients from Uppsala and Västerbotten).ParticipantsPatients (aged ≥18 years) with primary or secondary diagnoses of HF (≥2 International Classification of Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
2
15
1
Order By: Relevance
“… 16 Similar findings have been reported in Sweden. 17 Consistently with the higher comorbidity burden in HF versus non‐HF, in our analysis we showed that patients with HF were also more likely treated with non‐HF drugs, which further contributes to increasing costs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“… 16 Similar findings have been reported in Sweden. 17 Consistently with the higher comorbidity burden in HF versus non‐HF, in our analysis we showed that patients with HF were also more likely treated with non‐HF drugs, which further contributes to increasing costs.…”
Section: Discussionsupporting
confidence: 83%
“… 18 In Sweden, the total amount of all‐cause secondary care costs in the first year after HF diagnosis was €12 890/patient/year. 17 The cardiovascular inpatient care accounted for the largest part of the total secondary care costs (€11 578/patient/year) and exhibited a strong decline after the first year from diagnosis. 17 However, this declining trend in costs is limited to the individual longitudinal trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalizations due to HF represent 1–2% of all admissions, 1 and therefore, costs of HF are mainly driven by hospitalization. 43 After the initial diagnosis, HF patients are hospitalized on average about once a year due to the HF worsening. 44 Of note, HF hospitalization is associated with high 30 day readmission rate, up to 25%.…”
Section: European Epidemiological Data On Heart Failurementioning
confidence: 99%
“…3,8,26 Limitations of this study have been discussed in detail previously. 15,27 In short, the retrospective design of the present study is accompanied with challenges of identifying a cohort with a confirmed and validated diagnosis of HF, accounting for missing values for LVEF due to the absence of echo. Two diagnoses to define HF were expected to increase specificity, which might have excluded of more recent or milder cases of HF.…”
Section: Discussionmentioning
confidence: 99%